The people factor strengthening America by investing in public service - Bilmes, Linda (Brookings Institution Press, 2009)
"Presents a blueprint for reinvigorating the public sector based on 'The People Factor.' Shows why the U.S. personnel system needs reform, revealing the high price of inaction. Lays out specific steps to achieve the necessary gains, focusing on implementing 'best practices' from successful companies, the military, and high-performing government agencies"--Provided by publisher.